2003
DOI: 10.1046/j.1439-0434.2003.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ralstonia solanacearum in Soil and Weeds from Commercial Tomato Fields Using Immunocapture and the Polymerase Chain Reaction

Abstract: A detection assay for Ralstonia solanacearum in soil and weeds was developed by combining immunocapture and the polymerase chain reaction (IC-PCR). Anti-R. solanacearum polyclonal antibodies were produced in a white female rabbit and Dynal Ò superparamagnetic beads were coated with purified immu-noglobulinG (IgG). Using IC-PCR, the 718 bp target DNA was amplified at a detection threshold of approximately 10 4 colony-forming units (CFU) bacteria per millilitre of suspension. DNA was not amplified in soil suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…De Souza and Café-Filho (2003) reported that inoculation of plants of different botanical taxa including weeds such as Nicandra physalodes with a strain of Leveilula taurica indicated a wide host range. Amaranthus spinosus, Physalis minima and Euphorbia hirta had the highest incidence of Ralstonia solanacearum infection when weeds were tested from a commercial tomato field (Dittapongpitch and Surat 2003).These discoveries suggest that this weed may play a major role in survival of R. solanacearum between successive crops and cropping patterns. The South African biovar strain 3 of Pseudomonas solanacearum, which causes wilt in potatoes, was isolated from D. stramonium and Solanum nigrum (Swanepoel 1992).…”
Section: Introductionmentioning
confidence: 84%
“…De Souza and Café-Filho (2003) reported that inoculation of plants of different botanical taxa including weeds such as Nicandra physalodes with a strain of Leveilula taurica indicated a wide host range. Amaranthus spinosus, Physalis minima and Euphorbia hirta had the highest incidence of Ralstonia solanacearum infection when weeds were tested from a commercial tomato field (Dittapongpitch and Surat 2003).These discoveries suggest that this weed may play a major role in survival of R. solanacearum between successive crops and cropping patterns. The South African biovar strain 3 of Pseudomonas solanacearum, which causes wilt in potatoes, was isolated from D. stramonium and Solanum nigrum (Swanepoel 1992).…”
Section: Introductionmentioning
confidence: 84%
“…Según McGregor et al (1996) las sustancias inhibitorias desnaturalizan o se unen a la enzima ADN polimerasa, quelatan el cofactor de Mg ++ ó se unen directamente al ADN. Entre dichas sustancias se destacan los ácidos húmicos y fúlvicos presentes en la materia orgánica del suelo, los compuestos fenólicos generados en el metabolismo secundario de las plantas y los polisacáridos ácidos de alto peso molecular presentes en las paredes celulares de las bacterias y plantas (Dittapongpitch & Surat, 2003). Esta situación reafirma la necesidad de adelantar estudios como el aquí presentado, pues al no ser posible generalizar el empleo de un método determinado sobre diferentes tipos de plantas ó de suelos, se requiere del análisis particular de cada situación, más aún en casos tan determinantes como el que representa para el manejo de la enfermedad del Moko, la detección temprana de su agente causal.…”
Section: Discussionunclassified
“…(2000) detected lower levels of R. solanacearum (100 CFU g −1 soil) but, because of the high cross‐reaction rate, it was necessary to confirm the identities of fluorescent colonies using PCR techniques. Immunocapture followed by PCR detection was also reported recently, leading to a detection threshold of 10 4 CFU g −1 soil (Dittapongpitch & Surat, 2003). The sensitivity of serological methods for the detection of R. solanacearum in potato or in soil can be increased by applying an enrichment procedure, for example by incubating extracts in a selective broth (Elphinstone et al ., 1996; van der Wolf et al ., 1998; Priou et al ., 1999; Pradhanang et al ., 2000; Caruso et al ., 2002).…”
Section: Introductionmentioning
confidence: 83%